The alpha syllabus A handbook of human EEG alpha activity - Brown, Barbara B.; Klug, Jay W. (Thomas, 1974)
654 references with abstracts to "all known scientific reports on EEG alpha activity." Covers 1960-1972. Mostly English-language journal articles, although foreign languages and monographs are also covered. Topical arrangement under headings such as Measurement, Development, and Cognitive influences. Supplemental references without abstracts cover pre-1960 literature. Descriptor index.
Keywords: Electroencephalography -- Abstracts; Alpha-Rhythmus; Elektroencephalogramm; Alphasyllabus